Pengembangan Permainan Edukatif Ular Tangga “Eduta” Untuk Menstimulasi Aktivitas Gerak Anak Usia 5-6 Tahun - Maryamah, Elisa; Pramono; Tirtaningsih, Munaisra Tri (Innovative: Journal Of Social Science Research, 2024)
Snakes and ladders game is a board game divided into several boxes and in the box contains a picture of a number of ladders and snakes that connect to other boxes using ball numbers to determine how many steps the pieces must take. The purpose of the study was to determine the ability of children's motor activity through educational games and the feasibility of the educational game snakes and ladders "eduta". This study uses the Research and Development (R&D) method by synthesizing several proven research and development models, namely the Ploom Model (2007), the Kemp Model (2004), the Hanafin and Pack Model (1998) and the Borg and Gall model (1989, p.624) the development steps used include: 1) Needs analysis stage; 2) The desired aspirational model stage for early childhood education educators; 3) developing an initial or hypothetical model; 4) conducting expert testing of this prototype; 5) conducting small-scale testing of the test usage model, and 6) conducting field trials. Data obtained from experts include game experts, motor experts, and user experts (teachers). The instruments used in this research method are questionnaires and observation sheets. The data analysis techniques used are qualitative and quantitative analysis. The results of expert validation are as follows: (1) 93.725% stated by motor experts that the educational game of snakes and ladders is very valid, efficient, safe, and interesting to use, (2) 89.805% stated by game experts that the educational game of snakes and ladders is very valid, efficient, safe, and interesting, (3) 77.75% stated by user experts that the educational game of snakes and ladders is very valid, efficient, safe, and interesting. In the small group test, the following data were obtained: (1) 98.3% this educational game of snakes and ladders is safe for children aged 5-6 years, and in the large group test, the following data were obtained: (2) 97.8% this educational game of snakes and ladders is very suitable for use for children aged 5-6 years.